A diverse chasmataspidid (Arthropoda: Chelicerata) fauna from the Early Devonian (Lochkovian) of Siberia. (18th November 2013) - Marshall, David J.; Lamsdell, James C.; Shpinev, Evgeniy; Braddy, Simon J.; Dunlop, Jason
Abstract Examination of material held at the Palaeontological Institute, Moscow, enables the identification of two novel chasmataspidid species: Nahlyostaspis bergstroemi gen. et sp. nov. and Skrytyaspis andersoni gen. et sp. nov. 'Eurypterus' stoermeri and 'Tylopterella' menneri are both redescribed as chasmataspidids, having previously been assigned to Eurypterida. 'T'. menneri is transferred to the new genus Dvulikiaspis gen. nov. An identical prosomal structure is identified in 'Eurypterus' stoermeri and Heteroaspis novojilovi from the Devonian of Germany and the two species are synonymized, with 'E' stoermeri having priority. The previous synonymy of H. novojilovi with Diploaspis casteri is rejected. The presence of ophthalmic ridges is confirmed within Diploaspididae, and new structural characteristics of their bucklers are identified.